2009
DOI: 10.1590/s0102-33062009000300017
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento e uso de plantas em uma comunidade caiçara do litoral sul do Estado do Rio de Janeiro, Brasil

Abstract: A Área de Proteção Ambiental de Cairuçu (APA) localiza-se no município de Paraty, RJ. É uma unidade de conservação de uso sustentável e dispõe-se a proteger o ambiente natural e as comunidades caiçaras da região. O objetivo deste estudo foi realizar um inventário etnobotânico das plantas conhecidas e utilizadas pela comunidade caiçara que habita a praia de Martim de Sá. Moram no local 30 pessoas das quais 10 foram entrevistadas. As informações etnobotânicas foram obtidas através da observação participante e en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 16 publications
3
19
0
11
Order By: Relevance
“…A low number of plants with high UV was also observed in other studies which recorded less than five species with values higher than 1.0 (ALBUQUERQUE; ANDRADE; BORGES;PEIXOTO, 2009;GALEANO, 2000). This supports the idea that each informant bears a unique set of experiences on the roles played by plants to their well-being.…”
Section: Punica Granatumsupporting
confidence: 84%
See 3 more Smart Citations
“…A low number of plants with high UV was also observed in other studies which recorded less than five species with values higher than 1.0 (ALBUQUERQUE; ANDRADE; BORGES;PEIXOTO, 2009;GALEANO, 2000). This supports the idea that each informant bears a unique set of experiences on the roles played by plants to their well-being.…”
Section: Punica Granatumsupporting
confidence: 84%
“…Comparing diversity values with those of studies also conducted in communities located in the Atlantic Forest or in rural settlements, Shannon-Wiener and equitability values were somewhat high, with similar values to those of the other studies (Table 4) (AMOROZO, 2002;BORGES;PEIXOTO, 2009;PINTO;AMOROZO;FURLAN, 2006). High values of these indices link the areas to the populations with significant ethnobotanical knowledge (LIMA, et al, 2000), and were observed among the studied communities, because the Shannon index indicated the extent to which local diversity was explored by the population.…”
Section: Diversity and Similaritysupporting
confidence: 77%
See 2 more Smart Citations
“…In terms of authorization by governmental bodies, there were requirements in four journals: Revista Brasileira de Farmacognosia, Acta Amazônica, Anais da Academia Brasileira de Ciências, and Ethnobiology and Conservation. Within Acta Amazônica guidelines, there is a specific item concerning legal and ethical aspects, which clarifies the organs that are suitable Anderson 1977Miller et al 1989Grandi et al 1989 Rodrigues 1998 Negrelle & Fornazzali, 2007;Ribeiro et al 2007;Rodrigues & Carvalho 2007;Souza 2007;Vieira et al 2007;Yuyama et al 2007;Calábria et al 2008;Cunha-Lima et al 2008;Melo et al 2008;Miranda & Hanazaki, 2008;Rufino et al 2008;Santos et al 2008;Silva & Proença 2008;Baldauf et al 2009;Borges & Peixoto 2009;Castro et al 2009;Eichemberg et al 2009;Fonseca-Kruel et al 2009;Jesus et al 2009;Lanini et al 2009;Leitão et al 2009;Marchese et al 2009;Oliveira & Trovão 2009;Pilla & Amorozo 2009;Pires et al 2009;Santos et al 2009;Scoles 2009;Ustulin et al 2009.…”
Section: Resultsmentioning
confidence: 99%